The Perspectives of Biomarkers in Predicting the Survival of the Renal Graft - Aldea, Paul Luchian; Rachisan, Andreea Liana; Stanciu, Bogdan Ioan; Picos, Andrei; Picos, Alina Monica; Delean, Dan Ioan; Stroescu, Ramona; Starcea, Magdalena Iuliana; Borzan, Cristina Maria; Elec, Florin Ioan (Frontiers in Pediatrics, 2022)
Kidney transplantation (KT) is currently the elective approach for end-stage renal disease patients. Although it is a safe choice for these patients, the early complications can lead to graft dysfunction. One of the most redoubtable complications is delayed graft function (DGF), having no specific treatment. The effects of DGF on the graft survival are large enough in order to justify the formulation of specific biological protocols. Therefore, discovering biomarkers of acute impairment in renal transplanted patients is required. Creatinine is a poor marker to establish the kidney injury. Estimated glomerular filtration rate together with creatinine are readily to approximately measure the kidney function. Different serum and urine proteins are being studied as possible predictive biomarkers for delayed graft function. This review will concentrate on recent and existing research which provide insight concerning the contribution of some molecules for the estimation and evaluation of graft function after kidney transplantation. Further studies examining various aspects of DGF after KT are urgently needed to address a hitherto little-known clinical question.